The heist ebook - Du Brul, Jack (Isaac Bell, 2024)
Detective Isaac Bell faces an attack on the Federal Reserve in this all-new adventure in the #1 New York Times bestselling series from Clive Cussler. 1914: As America’s century of dominance dawns, the country’s greatest detective, Van Dorn agent Isaac Bell, is pitted against a master thief and his assassin accomplice. They’re plotting to pull off the greatest heist in America’s history: the theft of a billion dollars from the newly created Federal Reserve. When an aerial attack is launched against Woodrow Wilson’s yacht during a meeting among the Federal Reserve’s branch leaders, Bell thwarts it, only to find that the strike was just the opening of an even deadlier gambit. It’s up to Bell to find the link between the attack, the mysterious death of a Newport heiress, and growing evidence of an unimaginably audacious heist. Double-cross and betrayal are Bell’s stock and trade, but this time, the deeper he delves into the puzzle, the less he seems to understand. He is in a race against his most ruthless opponent yet, to prevent a financial panic that would bring the United States to its knees.